79.9k views
2 votes
How would you solve 2x^2 -4x -3 = 0

User Syldman
by
5.8k points

1 Answer

4 votes

ANSWER


x =1 +(1)/(2) √( 10) \: or \: x =1 - (1)/(2)\: √(10)

Step-by-step explanation

The given quadratic equation is


2 {x}^(2) - 4x - 3 = 0

This function is of the form:


a{x}^(2) + bx + c = 0

This implies that:

a=2, b=-4 and c=-3.

We can solve this equation using the quadratic formula:


x = \frac{ - b \pm \: \sqrt{ {b}^(2) - 4ac} }{2a}

We substitute the values into the quadratic formula to obtain;


x = \frac{ - - 4 \pm \: \sqrt{ {( - 4)}^(2) - 4(2)( - 3)} }{2(2)}


x = (4 \pm \: √( 40) )/(4)


x = (4 \pm \: 2√( 10) )/(4)


x =1\pm \: (1)/(2) √(10)


x =1 +(1)/(2) √( 10) \: or \: x =1 - \: (1)/(2) √(10)

User Bohemian
by
4.9k points